Interspecific differences in habitat selection of syngnathids in the Ria Formosa lagoon, Portugal - Mueller, Carolin (2019)
Interspecific patterns of local population abundances and differences in habitat preference of two sea grass resident pipefish species of the genus Syngnathus were investigated in a semi-protected lagoon system in Southern Portugal. The results of the combination of field surveys across different seagrass meadows and laboratory habitat choice experiments between May and September 2014 demonstrate that the pipefish population structure in a single-species meadow composed of Zostera noltei differed significantly from the ones in a single-species meadow of Cymodocea nodosa and a mixed meadow of both seagrasses. In addition, the two most abundant pipefish species, Syngnathus typhle and Syngnathus abaster, showed interspecific and intersexual differences in habitat selection both on a macro- and a microhabitat scale in laboratory experiments. The study suggests that in addition to the investigated structural characteristics of sea grasses (i.e. shoot length and density), other factors such as flow velocity may influence habitat selection of syngnathids. (C) 2017 Elsevier Ltd. All rights reserved.